FATIGUE ANALYSIS AND OPTIMIZATION OF TRANSVERSE STAILIZER BAR LINK BASED ON MEASURED LOAD SPECTRUM - LIU Zhilei; DU Jian; HAN Jie (Jixie qiangdu)
In order to solve fatigue fracture problem of the transverse stabilizer bar link of a pickup truck, taking the measured load spectrum as support, the fatigue analysis and structural improvement of bar link was carried out based on multi-body dynamics load decomposition method. The load spectrum acquisition test of stabilizer bar link was carried out, and the correlation analysis between sensor signals was conducted, and the validity of the collected signals was verified. Through the kinematics compliance（KC） test, the accuracy of suspension dynamics model was verified, by using virtual iteration method, the accuracy of the vehicle dynamic model is verified by the measured load spectrum signal as excitation. The critical load of bar link was obtained by means of multi-body dynamics load decomposition method, compression rod instability theory method and bench test method respectively, the strength of link was checked and compared with the measured load value, and the accuracy of the three methods was evaluated. The results show that multi-body dynamics load decomposition method can accurately predict the critical load, the bench test method have some errors, and the the compression rod instability theory cannot be directly used for strength check of link. Fatigue simulation and optimization of link were carried out by combining nominal stress method and load spectrum of multi-body dynamics decomposition. The fatigue mileage predicted by simulation is 12 143 km, the relative error value with real life is 14%, which proves validity of simulation method. The structural improvement of the dangerous part of link body port eliminates stress concentration of it, and makes the design life of link meet the service requirements.